Drug Abuse of Professional Drivers: Experience from Referral Dope Test (Bangladesh Medical Journal, 2024)
In Bangladesh, drug abuse is one of the dangerous problems among drivers that hamper road safety and make government worry. In that context, this cross-sectional study was conducted in National Institute of Laboratory Medicine and Referral Center (NILMRC) and aims to determine the proportion of drug abuser among professional drivers in Bangladesh. This study also addressed to recognize the various types of abused drugs, the pattern and the trend of drug abusers during study period. Data were collected from online data server of NILMRC during the period of July to December 2022. Bangladesh Road Transport Authority (BRTA) customarily refers urine samples of drivers to NILMRC for dope test. Dope tests were performed in immunochromatographic test (ICT) device and semi-auto analyzer. Dope results and demographic data of drivers were well-kept-up in online server for electronic transfer and use of data. Commonly abused drugs in Bangladesh such as, cannabinoids, amphetamines, opiates, benzodiazepines and alcohol were assessed. A total of 70866 drivers had been tested for six months of study period among them 2720 (3.81%) were found dope test positive. Considering monthly trends from July to December 2022 the highest incidence were found in December where 473 (4.58%) of 10323 drivers were dope test positive; however in November 639 (4.56%) of 14,017, in September 682 (4.07%) of 16757, in October 551(3.62%) of 15221, in August 320 (3.42%) of 9348, then less incidence were found in July 55 (1.05%) of 5200 drivers had been tested positive. There was an increase number of test positive cases were detected during the period from July to December.  The highest number drug abuser that is more than two-third (70%) of drivers were found among young adult age group (25-44) years. The five types of abused drugs were tested; among those the highest proportion (91.5%) of abused drug was Cannabinoids, then Benzodiazepines was 5.5%, Amphetamine was 1.3%, Opiates was 1% and Alcohol was 0.8%. No female drivers were found test positive. Cannabinoids was the most common drug of abuse among drivers referred by BRTA, Bangladesh. During this study, there was challenge to different kind illegal means. If the illegal means could be resolute then the data of positive finding would be higher than this finding. So implementation online registration, proper identification by finger print or retinal scanning and providing online reports may minimize the illegal means.Bangladesh Med J. 2023 Jan; 52(1): 1-5